Experimental Research on Seismic Performance of Damaged Brick Walls Strengthened with Embedded Horizontal Steel Bars - Liu Tingbin; Jia Rubo; Pei Xianke; Zhang Jiawei; Zhao Jianchang (Advances in Civil Engineering)
Six brick masonry specimens (two unreinforced specimens, two reinforced specimens, and two specimens reinforced after being damaged), which have different aspect ratios, were tested under low-frequency cyclic loading. The seismic performances of these specimens, including failure characteristics, deformation capacity, carrying capacity, energy dissipation capacity, hysteresis characteristics, and stiffness degradation, were analyzed. The following results were obtained: the ductility of the damaged walls could be significantly improved after they were reinforced with embedded horizontal steel bars; the ultimate shear capacity of the damaged brick masonry walls with the aspect ratios of 1.8 and 0.5 was improved by 6.8% and 4.7%, respectively; the displacement corresponding to the ultimate bearing capacity was close to that of the unreinforced brick masonry wall; the hysteresis loop of the reinforced wall became plumper and encompassed a larger area; after the ultimate load was reached, a clear yielding platform appeared in the skeleton curve of the reinforced wall; the reinforced wall exhibited good ductility, after entering plastic stage; the energy dissipation capacity of the reinforced wall was significantly greater than that of the unreinforced wall. In conclusion, the seismic performance of the damaged brick masonry wall can be improved by embedding horizontal steel bars, and this reinforcing method can be applied in the postseismic reconstruction process.